1998
DOI: 10.1016/s0014-5793(98)00389-5
|View full text |Cite
|
Sign up to set email alerts
|

Homologous p35 proteins of baculoviruses show distinctive anti‐apoptotic activities which correlate with the apoptosis‐inducing activity of each virus1

Abstract: The anti-apoptotic activity of p35s from two baculoviruses, Autographa californica nucleopolyhedrovirus (AcNPV) and Bombyx mori NPV (BmNPV), was compared in mammalian cells. AcNPV p35 efficiently blocked apoptosis induced by caspase overexpression, but BmNPV p35 did so very poorly. Analysis of chimeric p35s and in vitro cleavage of wild type p35s suggest that the cleavage efficiency of p35 correlates with the blocking activity. Single amino acid substitutions of BmNPV p35 with those observed in AcNPV p35, howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 28 publications
(50 reference statements)
0
14
0
Order By: Relevance
“…This group also showed that AcMNPV v-UBI may function in baculovirus replication to block the destruction of shortlived proteins by the host degradative pathway (Haas et al, 1996). Amino acid differences in some proteins have been shown to result in the phenotypic discrepancies between AcMNPV and BmNPV (Kamita & Maeda, 1997;Katou et al, 2010;Katsuma et al, 2006b;Morishima et al, 1998;Nakanishi et al, 2010). Despite the fact that the amino acid sequences of v-UBI are completely identical between these two viruses, the roles of v-UBI may be different in the infection cycle of each NPV.…”
Section: Discussionmentioning
confidence: 99%
“…This group also showed that AcMNPV v-UBI may function in baculovirus replication to block the destruction of shortlived proteins by the host degradative pathway (Haas et al, 1996). Amino acid differences in some proteins have been shown to result in the phenotypic discrepancies between AcMNPV and BmNPV (Kamita & Maeda, 1997;Katou et al, 2010;Katsuma et al, 2006b;Morishima et al, 1998;Nakanishi et al, 2010). Despite the fact that the amino acid sequences of v-UBI are completely identical between these two viruses, the roles of v-UBI may be different in the infection cycle of each NPV.…”
Section: Discussionmentioning
confidence: 99%
“…A p35 mutant of AcMNPV does not produce OBs in Spodoptera frugiperda cells, whereas the BmNPV p35 mutant can grow normally and produce OBs in BmN cells (18). Biochemical studies revealed that AcMNPV P35 efficiently blocks apoptosis induced by caspase overexpression but that BmNPV P35 does so very poorly, suggesting that BmNPV P35 is weaker than AcMNPV P35 in terms of the suppression of caspase-induced apoptosis (40). Also, a BmNPV possessing AcMNPV gp64 was shown to produce more BVs in BmN cells than repaired BmNPV (21).…”
Section: Generation Of Recombinant Bmnpvs Expressing the Fp25kmentioning
confidence: 99%
“…Although these ORFs were closely related, the changes present could influence the function of the protein produced. For example, several amino acid substitutions found in BmNPV ORF112 (p35) compared with Ac135 (p35) (91 % amino acid identity) result in a decrease in its ability to inhibit apoptosis by interacting with caspase-1 in mammalian cells (Morishima et al, 1998). The evolution of a less-efficient BmNPV p35 could result in BmNPV causing a milder apoptotic response compared with AcMNPV.…”
Section: Comparison Of Homologous Orfs Between Bmnpv and Acmnpvmentioning
confidence: 99%